Treatment Options for Brachial Plexus Injuries - Sakellariou, Vasileios I. (Hindawi Publishing Corporation, 2014)
The incidence of brachial plexus injuries is rapidly growing due to the increasing number of high-speed motor-vehicle accidents. These are devastating injuries leading to significant functional impairment of the patients. The purpose of this review paper is to present the available options for conservative and operative treatment and discuss the correct timing of intervention. Reported outcomes of current management and future prospects are also analysed.